IMPLEMENTASI METODE FUZZY LOGIC BERBASIS INTERNET OF THINGS PADA ALAT PENYIRAMAN OTOMATIS TANAMAN PEPAYA CALIFORNIA - Wijaya Kusuma, I Wayan Angga; Afriliana Kusumadewi; Naufal Rofii, (Journal of Computer Science and Technology (JCS-TECH), 2025)
Watering is a crucial factor in California papaya plant maintenance. Soil moisture content is a major limiting factor in California papaya cultivation, where maintaining consistent moisture is crucial for optimal growth, flower formation, and fruit productivity. Soil moisture should not be too dry, as dry soil can slow the development of California papaya plants. Conversely, overwatering can cause California papaya plants to die due to excessive root absorption. This study aims to implement the Fuzzy Logic method in an Internet of Things-based automatic watering device for California papaya plants. Using the Fuzzy Logic method can make the agricultural system more effective and efficient. The results of this study were able to effectively monitor California papaya plants. The output generated by this device was able to display sensor readings on a 4x20 I2C LCD and displayed in the Blynk application. The results of soil moisture measurements under normal conditions were 20%, dry conditions 4%, and wet conditions 80%. The results of soil temperature measurements using the DS18B20 sensor had an average error of 1.56%. The average error of the soil pH sensor under normal conditions is 2.66%, under acidic soil conditions it is 4.65%, and under growing media with pH-enhancing fertilizer it is 2.56%. The water pump will turn on when the fuzzy logic system reads soil moisture in the dry (0%-40%), moist (40%-70%) and wet (70-80%) categories, and the pump will automatically turn off when it reaches the wet (70-80%) category.